The Effect of Pedagogical Competence and Professional Competence of Students After Teaching Assistance on Interest in Becoming ICT Teachers and Teaching Readiness of Informatics Engineering Education Students, Universitas Negeri Malang - Herwanto, Heru Wahyu; Irianto, Wahyu Sakti Gunawan (Universitas Negeri Malang, 2024)
Survey findings indicate that some Informatics Engineering Education students show low interest in pursuing a teaching career, leading to reduced motivation, enthusiasm, and teaching readiness. This lack of interest negatively affects their pedagogical and professional competence. The Teaching Assistance Program was created for educational students to hone their teaching skills and develop their capabilities through curriculum development and implementation. This study aims to:(1) reveal the effect of pedagogical competence on interest in becoming an ICT teacher and teaching readiness; (2) reveal the effect of professional competence on interest in becoming an ICT teacher and teaching readiness; (3) reveal the effect of interest in becoming an ICT teacher on teaching readiness; (4) reveal the effect of pedagogic competence and professional competence on teaching readiness through the intervening variable interest in becoming a teacher. The study found that professional competence significantly influences students’ interest in becoming ICT teachers, while pedagogical competence significantly affects teaching readiness. Interest in becoming an ICT teacher also has a strong positive effect on teaching readiness. Additionally, professional competence indirectly enhances teaching readiness through increased career interest, whereas pedagogical competence shows no significant indirect effect through interest.